2018
DOI: 10.1093/jhps/hny042
|View full text |Cite
|
Sign up to set email alerts
|

Upsloping lateral sourcil: a radiographic finding of hip instability

Abstract: While radiographic findings of frank hip dysplasia are well defined, there is a lack of diagnostic criteria for patients with radiographically ‘normal’ hips who have borderline morphologic deficits and clinical instability. In this study, we aim to define and validate a new radiographic finding associated with hip instability known as the upsloping lateral sourcil (ULS). Patients (316) were reviewed for lateral center edge angles, generalized joint laxity assessed with the Beighton Hypermobility Score and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…37 Thus, additional radiographic parameters should be used to assist in the diagnosis of borderline or frank hip dysplasia, in particular the ACEA, 37 anterior wall index, 37 Tönnis angle, 37,49 iliofemoral line, 28 a broken Shenton line, 23 and the presence of an upsloping lateral sourcil. 57…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Thus, additional radiographic parameters should be used to assist in the diagnosis of borderline or frank hip dysplasia, in particular the ACEA, 37 anterior wall index, 37 Tönnis angle, 37,49 iliofemoral line, 28 a broken Shenton line, 23 and the presence of an upsloping lateral sourcil. 57…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the LCEA, supplementary radiographic parameters from plain radiographs used to assess for acetabular dysplasia include the Tönnis angle, ACEA, anterior and posterior wall index, acetabular index, iliofemoral line, 28 and an upsloping lateral sourcil 54,57 (Figure 1). In a retrospective review of 98 patients with hip pain and an LCEA between 18° and 25°, McClincy et al 37 identified the ACEA and anterior wall index as independent factors predicting which patients underwent hip arthroscopy versus PAO.…”
Section: Defining Frank Hip Dysplasia and Bhd With Radiographic Parammentioning
confidence: 99%
“…Our method of grouping, based on accepted current literature, utilizes LCEA ≤20 as a marker for instability and LCEA >20 to indicate the absence of instability. However, the true assessment of hip instability goes far beyond the measured LCEA and includes acetabular version, femoral torsion, congruency of articulation, percentage medialization of the iliofemoral line, 16 presence of an upsloping lateral sourcil, 37 Beighton ligamentous laxity score, and clinical range of motion. In actual surgical practice, the senior author implements all of these important parameters in arriving at a treatment plan that is tailored to each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, there was no correlation relationship between the supra‐peripheral or supra‐central regional topographic‐acetabular curvature and LCEA or ARO. Meanwhile, it has been reported that the upsloping lateral sourcil of the acetabular rim is often observed in AP radiographs of the borderline and the frank dysplastic hips 38 . In our study, we evaluated the zonal‐acetabular curvature, assuming that the lunate surfaces in the zone are spherical surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the acetabular rim morphology can affect the measurements of topographic‐acetabular radius of curvatures. Furthermore, it has been pointed out that the upsloping lateral sourcil may be associated with the enlarged attachment of the labrum in the dysplastic hips 38–40 . Since the purpose of this study was to evaluate the difference of the topographic‐acetabular curvatures in the acetabulum, we focused on the measurement range on the lunate surface.…”
Section: Discussionmentioning
confidence: 99%